High performance liquid chromatographic method for the detection of some neurotransmitters in blood samples using fluorescence detector - Helal Uddin, A.B.M.; Saeed, Mohammad; Khan, Umeed Ali (2010)
A reverse phase high performance liquid chromatographic method for the detection of the neurotransmitters namely serotonin, tryptophan and dopamine in human blood samples has been developed. Spiked standard samples were analysed using a fluorescence detector after chromatographic separation. For the analytes a working range of 2.5 ng/mL to 25 ng/mL were found suitable for the application. For chromatographic separation C18 type of column showed the better separation results and was used for the study. Mobile phase was optimised to 97% phosphate buffer and ion pairing reagent (pH adjusted to 5.5) together with 3% acetonitrile. Sample preparation step was found to be more effective with protein precipitation method than the solvent extraction method. Two protein precipitation methods were compared and found that perchloric acid method was more suitable than that of acetonitrile method. Intra and inter day precision of the analytes were determined and the coefficient of variation (CV) were less 15% which is within the acceptable limit of standard guidelines. Specificity of the analytes was established by comparing the standard peaks with the blank plasma chromatogram. The analysis results showed that the method is specific, accurate and reliable for the quantification of the analytes in human samples.